Navigating the Complexity of Gender and Sexual Identities in 2gether the Series - Daniswara, Royhan Abdiel; Aprilia, Aindra; Kurniawan, Sahara Ramanda Gibtha (Alphabet, 2023)
This study investigates the complexity of gender and sexual identities portrayed in LGBTQ+ series, 2gether the Series, by applying Stuart Hall’s representation theory. The series is chosen due to its discourses that portray sexual and gender identities. This study is a qualitative research, so this study focuses on the dialogues and discourses. Therefore, gender and sexual identities are investigated to find out how popular culture like 2gether the Series represents them in contemporary media. The result shows that the series challenges the traditional norms regarding sexual identities present in scenes that highlight fluidity, gender roles, and coming out. The researchers also find that several scenes in the series reinforce some of the stereotypes by embracing them in the discourse among the characters. Then, the researchers apply representation theory to analyze the data. This study concludes that gender and sexual identities in 2gether the Series are depicted in a complex manner, challenging traditional norms while also perpetuating certain stereotypes, which highlights the ongoing evolution of perceptions and acceptance in contemporary media.